Health Risk Assessment (HRA) in Home-Based Ironing Businesses: Risk Identification, Intervention, and Evaluation in Johar Baru District, Central Jakarta - Alfares, Heru; Darmaputra, Irawadi; Isbayuputra, Marsen; Ilyas, Muhammad (UI Scholars Hub, 2025)
Background Home-based ironing businesses in Johar Baru District, Central Jakarta, are part of the informal sector, vulnerable to health risks due to suboptimal working conditions. This study aims to identify, assess, and control health risks through a Health Risk Assessment (HRA) approach. Methods Research methods include direct observation, interviews, environmental measurements, health screenings, and ergonomic surveys using the BRIEF (Baseline Risk Identification of Ergonomic Factor) instrument. Results The results indicate that the temperature in the ironing area reaches 33°C, exceeding the comfort standard, and that 80% of workers have dark yellow urine, indicating a high risk of dehydration. Risk assessment using the GlaxoSmithKline Environment, Health, and Safety (GSK EHS) risk matrix identifies dehydration as the highest risk (score 12, High), followed by varicose veins and muscle pain (score 9, Medium). Interventions such as hydration education, provision of 1000 ml water bottles, and reminder alarms effectively improved workers' hydration status, with urine color changing from dark yellow to light yellow. However, limitations in controlling high temperatures and potential bias in intervention evaluations remain challenges. Conclusion This study recommends installing fans, ergonomic interventions, and regular monitoring by community health centers to create a safer and healthier work environment. The findings contribute significantly to the development of occupational health and safety (OHS) models in the informal sector and to the promotion of evidence-based approaches in health risk management.